The utility of ketones at triage: a prospective cohort study. Issue 12 (3rd July 2020) - Durnin, Sheena; Jones, Jennifer; Ryan, Emer; Howard, Ruth; Walsh, Sean; Dawkins, Ian; Blackburn, Carol; O'Donnell, Sinead M; Barrett, Michael J
Abstract : Objective: To establish the relationship between serum point-of-care (POC) ketones at triage and moderate-to-severe dehydration based on the validated Gorelick Scales. Design, setting and patients: Prospective unblinded study from April 2016 to February 2017 in a paediatric emergency department. Patients aged 1 month to 5 years, with vomiting and/or diarrhoea and/or decreased intake with signs of moderate or severe dehydration or clinical concern for hypoglycaemia were eligible. Main outcome measures: The primary outcome was to describe the relationship between triage POC ketones to the two Gorelick Scales. Secondary outcomes were to examine the response of ketone levels to fluid/glucose administration and patient disposition. Results: One-hundred and ninety-eight patients were included; median age 1.8 years. The median triage ketones were 4.6 (IQR 2.8–5.6) mmol/L. A weak correlation was identified between triage ketones and the 10-point Gorelick Scale (Spearman's ρ=0.217, p = 0.002), however no correlation between triage ketones and the 4-point Gorelick Scale was identified. Those admitted had median triage ketones of 5.2 (IQR 4–6) mmol/L and repeat ketones of 4.6 (IQR 3.3–5.7) mmol/L compared with 4.2 (IQR 2.4–5.3) mmol/L and 2.9 (IQR 1.6–4.2) mmol/L in those discharged home. Conclusion: No correlation between triage POC ketones and the 4-point Gorelick Scale was established. POC ketones at triage have poor accuracy for predicting hospital admission. The elevated profile of POC ketones in non-diabetic children with acute illness suggests a potential target of tailored treatments for further research.